1999
DOI: 10.1046/j.1365-3091.1999.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Soft‐sediment deformation structures in late Albian to Cenomanian deposits, São Luís Basin, northern Brazil: evidence for palaeoseismicity

Abstract: Soft‐sediment deformation structures from the Alcântara Formation (late Albian to Cenomanian), São Luís Basin, northern Brazil, consist of (1) contorted structures, which include convolute folds, ball‐and‐pillow structures, concave‐up paths with consolidation lamination, recumbently folded cross‐stratification and irregular convolute stratification that grades into massive beds; (2) intruded structures, which include pillars, dykes, cusps and subsidence lobes; and (3) brittle structures, represented by fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
0
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(107 citation statements)
references
References 46 publications
(87 reference statements)
6
95
0
6
Order By: Relevance
“…Some structures are remaining connected to the overlying bed or the others are completely isolated from the bed. These structures in Lake Van sediments are very similar to presented in previous works (Hempton et al, 1983;Allen, 1986;Rossetti, 1999). Ball and pillow structures occur with liquefaction of unconsolidated sediments.…”
Section: Ball and Pillow Structuressupporting
confidence: 88%
See 2 more Smart Citations
“…Some structures are remaining connected to the overlying bed or the others are completely isolated from the bed. These structures in Lake Van sediments are very similar to presented in previous works (Hempton et al, 1983;Allen, 1986;Rossetti, 1999). Ball and pillow structures occur with liquefaction of unconsolidated sediments.…”
Section: Ball and Pillow Structuressupporting
confidence: 88%
“…Deformation structures exist in different levels of these shallow water deposits with the other sedimentary structures as cross-beds and wave ripples. Soft sediment deformation structures are classified differently according to morphologic properties or occurrence processes of the structure (Rossetti, 1999;Dramis & Blumetti, 2005;Neuwerth et al, 2006;Taşgın & Türkmen, 2009). In this study, soft sediment deformation structures, observed in lacustrine deposits of Lake Van, were classified as contorted structures (simple-complex convolute bedding and ball-pillow structures), load structures (flame structures) and water escape structures (dish and pillar structures).…”
Section: Deformation Structures (Seismites)mentioning
confidence: 99%
See 1 more Smart Citation
“…The generating mechanism of convolute structures is linked to fluidization processes, which create gravitational instabilities [73][74][75]. The triggering mechanism of these structures is often related to processes of sediment gravity flows, overloading of sandstone beds [e.g.…”
Section: S 1 Facies: Ungraded-to Graded Coarse-to Fine-grained Sandstmentioning
confidence: 99%
“…Dokładny opis litofacjalny, a następnie interpretacja genetyczna warunków środowiska jest niezbędna do odczytania prawidłowych implikacji paleogeograficznych. Powszechnie wiadomo, że struktury deformacyjne spowodowane rozchodzeniem fali sejsmicznej zapisują się przede wszystkim w osadach uwodnionych i udział wody jest niezbędny do ich powstania (Lowe 1976;Allen 1982;Rossetti 1999;Owen 1996;Van VlietLanoë i in. 2004).…”
Section: Analiza Litofacjalna Osadówunclassified